2018
DOI: 10.1177/1541931218621026
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Team Information

Abstract: This paper describes how meaning can be extracted from large-scale dynamical data to make inferences about teamwork that are useful in both the theoretical and practical sense. The dynamics of an anesthesiology team are viewed from the perspectives of: 1) changes in the team’s neurodynamic organizations with large and small changes in the task; 2) how team member’s neurodynamics contribute to team neurodynamics; 3) the relationships between task events, heart-rate and neural dynamic organizations; 4) the linka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The team neurodynamics were separated into those of each team member (Stevens & Galloway, 2017; Stevens, Galloway, & Willemsen-Dunlap, 2018) which provided profiles of each persons’ neurodynamics. From Figure 4a, the AN and circulating nurse (CN) who had previously worked closely together were also well coordinated during the simulation with overlapping NI profiles during the ITB-1, Crash Cart, and ITB-2 segments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The team neurodynamics were separated into those of each team member (Stevens & Galloway, 2017; Stevens, Galloway, & Willemsen-Dunlap, 2018) which provided profiles of each persons’ neurodynamics. From Figure 4a, the AN and circulating nurse (CN) who had previously worked closely together were also well coordinated during the simulation with overlapping NI profiles during the ITB-1, Crash Cart, and ITB-2 segments.…”
Section: Resultsmentioning
confidence: 99%
“…This will enable cognitively informed task designs and accelerate the rates of team and team-member learning by focusing on the cognitively relevant properties of performance. They will likely shape the evolution of existing theories of teamwork and the creation of new performance measures and teaching practices; these data will also increase the transparency of human states enabling effective machine-human collaborations (Stevens, Galloway, Willemsen-Dunlap, Gorman, & Halpin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that signals other than verbal communication might be needed to track real-time implicit coordination. For instance, we detected the patient seizing perturbation in Figure 5 using neural and heart rate synchronization but not speech (Stevens, Galloway, Willemsen-Dunlap et al, 2018) and have observed that neural synchronization and speech are mutually entraining (Gorman et al, 2016). Thus, we think aligning communication dynamics with neurodynamics, heart rate variability, and other less overt coordination markers could help address the false negative observed in Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…We present neurodynamic examples from multiple tasks to show the generality of the findings. The subjects, and task details for the Map Navigation Task (Stevens & Galloway, 2015), Submarine Navigation, Healthcare (Stevens & Galloway, 2017;Stevens, Galloway, Halpin & Willemsen-Dunlap, 2016;Stevens, Galloway & Willemsen-Dunlap, 2018) and the live patient surgical operation have been previously described (Stevens & Galloway, 2017;. Brief task descriptions summaries are included when referring to new findings.…”
Section: Teams and Tasksmentioning
confidence: 99%
“…These periods of neurodynamic organization can be visualized as metastable attractor states and quantitated as described below, enabling comparisons across team members, teams and training situations (Stevens, Galloway & Willemsen-Dunlap, 2018). The temporal organizations seem to be a general property of teamwork being observed in military, healthcare and pre-college teaming (Stevens & Galloway, 2017), and their presence during important periods of a live patient surgery extends their significance to the real world .…”
Section: Introductionmentioning
confidence: 99%